SOLUBILITY ENHANCEMENT OF POORLY WATER SOLUBLE DRUGS - Tushar Gohil (Indonesian Journal of Pharmacy, 2014)
Aqueous solubility is a limiting factor in the oral bioavailability of a certain class of poorly water soluble drugs. A consequence of low aqueous solubility is a slow dissolution rate. For the drugs with low aqueous solubility and high permeability the dissolution rate will be the rate limiting step for absorption. The most successful techniques that are employed for dissolution enhancement are micronization, formulation of amorphous systems and cyclodextrins containing dosage forms. This combined approaches to improve the dissolution of some poorly soluble drugs. Micronization increases the dissolution rate of drugs through increased surface area. The high surface area of drug micro/nano particles renders them thermodynamically unstable, promoting agglomeration and crystal growth. Microparticles of the poorly water soluble drugs were produced by the supercritical antisolvent method and simultaneously mixed with pharmaceutical excipients in a single step to prevent the drug agglomeration of drug particles. In the third approach cyclodextrins (CDs) were used as pharmaceutical solubilizers and inclusion complexes of drugs with β-CD.Key words: micronization, supercritical antisolvent, cyclodextrins